HUBUNGAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SEKOLAH YAYASAN SANTO ANTONIUS JAKARTA - sukarman, yohanes (Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas, 2018)
This study aimed at determining the relationship between organizational culture with teachers’ performance. The research was conducted among teachers of St. Anthony Foundation, Jakarta.  A research method used in this study was a correlational approach. This research involved 40 teachers of St. Anthony Education Foundation as research population.   Analytical requirement testing was done by using normality and linearity test. The result showed that the study had a normal distribution; the variables relationship was linear. The results show that there is a positive and significant relationship between organizational culture and teachers’ performance. It can be seen from the value of the correlation coefficient (r) of 0,564. It means that the correlations are positive and strong. If the culture of the organization is better, the performance of the teachers will be better too. Thus, the better the organizational culture was in proportion to the performance of the teachers at St. Anthony Education Foundation. Based on the results the researcher suggests that school principals need to improve teachers' performance by creating and improving conducive situation of organizational culture through reflection. This study proved the existence of a positive and significant relationship between organizational culture with teachers’ performance at St. Anthony Foundation Jakarta.